Status of the direct measurements of 18O(p, γ)19F and 23Na(p, γ)24Mg cross sections at astrophysical energies at LUNA. (April 2016) - Boeltzig, A; Pantaleo, F R; Best, A; Imbriani, G; Junker, M
Abstract: 18 O(p, γ) 19 F and 23 Na(p, γ) 24 Mg are reactions of astrophysical interest for example in AGB star scenarios. The rates of both reactions are potentially influenced by low-energy resonances for whose strengths either exist only values with large uncertainties, upper limits or even contradictory claims. Measurements at the Laboratory for Underground Nuclear Astrophysics (LUNA) aim at a direct observation of these low-energy resonances, and additional cross section measurements to aid a more precise determination of the reaction rates in astrophysical scenarios. We report the experimental setup and the status of the ongoing measurements of the two reactions at LUNA.